Testing Finch's hypothesis: The role of organismal modularity on the escape from actuarial senescence. (13th January 2020) - Bernard, Connor; Compagnoni, Aldo; Salguero‐Gómez, Roberto
Abstract: Until recently, senescence was assumed to be a universal phenomenon. Evolutionary theories of senescence predict that no organism may escape the physiological decline that results in an increase in mortality risk and/or decline in fertility with age. However, evidence both in animals and plants has emerged in the last decade defying such predictions. Researchers are currently seeking mechanistic explanations for the observed variation in ageing trajectories. We argue that the historical view on the inevitability of senescence is due, in part, to the development of its classical theories, which targeted primarily unitary organisms. In unitary species, the integration of resources and functions is high, and adult size is determined. In contrast, the architecture of modular organisms is indeterminate and built upon repeated modules. The isolation of mortality risk in species like hydra ( Hydra spp.) or creosote brush Larrea tridentata may explain their null or even negative senescence. Caleb Finch hypothesized three decades ago that species with the ability to compartmentalize risk may escape senescence. Here, we first review the evidence on organisms that slow down or even avoid senescence in the context of their architecture, along a continuum of unitarity‐modularity. Then, we use open‐access databases to comparatively analyse various moments of senescence and link longevity to the degree of anatomical modularity. Our analysis compares the pace of senescence across 138 plants and 151 animals, and the shape of senescence across a subset of these. Our comparative analysis reveals that plant species that are more modular do indeed tend to escape from senescence more often than those that are unitary. The role of modularity in animal senescence is less clear. In light of novel support for Finch's hypothesis across a large diversity of plant species, and with less conclusive findings in animals, we identify new research directions. We highlight the opportunities related to age‐dependent mortality factors. Other areas for further research include the role of modularity in relation to endocrine actions, and the costs of modular anatomies. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Abstracto: Hasta recientemente, la senescencia fue asumida como un fenómeno universal. Las teorías sobre las evolución de la senescencia predicen que ningún organismo puede escapar el declive fisiológico que resulta en un incremento del riesgo de mortalidad y/o declive en fertilidad con aumentos en edad. Sin embargo, la última década ha sido testigo de distintas lineas de evidencia en animales y plantas que desafían dichas prediciones. Los investigadores de senescencia están actualmente explorando mechanismos que expliquen la variación en trayectorias demográficas observadas en la naturaleza. Aquí nosotros discutimos que la perspective histórica sobre la inevitabilidad de la senescencia se debe, en parte, al desarrollo de las teorías clásicas, las cuales se centraron principalmente en organismos unitarios. En especies unitarias, hay una alta integración de recursos y funciones, y el tamaño en la madurez está pre‐determinado. En contraste, la arquitectura de los organismos modulares es indeterminada y está basada en la reiteración de módulos. El aislamiento del riesgo de mortalidad en especies como hidras ( Hydra spp.) o la gobernadora Larrea tridentata puede explicar trayectorias de senescencia nula o incluso negativa. Hace tres decadas, Caleb Finch hipotetizó que las especies con la capacidad de compartimentar el riesgo pueden escapar de la senescencia. En este manuscrito, primero revisamos la evidencia sobre organismos que desaceleran o incluso escapan de la senescencia en el contexto de su arquitectura, a lo largo de un continuo de unitariedad‐modularidad. Luego, utilizamos bases de datos de acceso público para analizar comparativamente varios momentos de senescencia y vincular la longevidad con el grado de modularidad anatómica. Nuestro análisis comparan la velocidad de senescencia en 138 plantas y 151 animales, y la forma de las trayectorias de senescencia en un subconjunto de éstas especies. Nuestro análisis comparativos revelan que las especies de plantas que son más modulares tienden a escapar de la senescencia con más frecuencia que las que son unitarias. El papel de la modularidad en la senescencia animal es menos claro. A la luz del novedoso apoyo a la hipótesis de Finch en una gran diversidad de especies de plantas, y con hallazgos menos concluyentes en animales, identificamos nuevas direcciones de investigación. Destacamos las oportunidades relacionadas con los factores de mortalidad dependientes de la edad. Otras áreas para futuras investigaciones incluyen el papel de la modularidad en relación con las acciones endocrinas y los costos de las anatomías modulares. Astratto: Fino a tempi recenti, la senescenza era considerata come un fenomeno universale. Le teorie sull'evoluzione della senescenza predicono che nessun organismo possa evitare il declino fisiologico originato da un aumento del rischio di mortalita e/o da un declino della fertilita' con l'avanzare dell'eta'. Tuttavia, negli ultimi dieci anni sono emerse evidenze contrarie a questa predizione sia in animali che in piante. Oggi i ricercatori stanno cercando spiegazioni sui meccanismi che possano spiegare la variazione nei processi di invecchiamento. Argomentiamo che la nozione sull'inevitabilita' della senescenza sia dovuta, in parte, alle teorie classiche focalizzate su organismi unitari. In specie unitarie, l'integrazione delle risorse e delle funzioni e' alta, e la dimensione degli individui adulti e' predeterminata. Al contrario, l'architettura degli organismi modulari e' indeterminata, ed e' costituita da diversi moduli ripetuti. Questi moduli possono isolare il rischio della mortalita', fatto che puo' spiegare la senescenza nulla o negativa osservata in specie come l'idra (Hydra spp.) o nell'arbusto Larrea tridentata. Trenta anni fa, Caleb Finch ipotizzo' che le specie con l'abilita' di isolare il rischio di mortalita' possano evitare la senescenza. In questo articolo, passiamo prima in rassegna l'evidenza riguardante gli organismi che rallentano o evitano la senescenza nel contesto della loro architettura, lungo un continuo che va dagli organismi unitari a quelli modulari. Poi usiamo database ad accesso libero per collegare il tasso di senescenza e la longevita' degli organismi al loro tasso di modularita' anatomica. La nostra analisi compara il tasso di senescensa di 138 piante e 151 animali, e la forma di senescenza in un sottoinsieme di queste specie. Questa analisi comparativa rivela che le specie vegetali che sono piu' modulari tendono ad evitare la senescenza piu' frequentemente di quelle che sono unitarie. Il ruolo della modularita' nella senescenza animale e' meno chiaro. Alla luce di questa nuova evidenza a supporto dell'ipotesi di Finch, basata su una grande diversita' di specie vegetali, e alla luce di risultati meno decisivi negli animali, identifichiamo nuove direzioni di ricerca. Sottolineiamo opportunita' di ricerca legate ai fattori di mortalita' dipendenti dall'eta'. Altre aree di ricerca futura includono il ruolo della modularita' in relazione alle azioni endocrine, e il costo delle anatomie modulari. A free Plain Language Summary can be found within the Supporting Information of this article.